Demonstration of binding of dengue virus envelope protein to target cells. - Chen, Y (1996)
The nature of the initial interaction of dengue virus with target cells and the extent to which this interaction defines tropism are unknown. Infection of some cells may involve antidengue antibody-mediated immune adherence to cells bearing immunoglobulin Fc receptors; however, this mechanism does not explain primary infection or the infection of cells without Fc receptors. We hypothesized that dengue virus envelope protein mediates initial binding to target cells. To test this hypothesis, a recombinant chimeric form of dengue type 2 virus envelope protein was used as a probe to investigate binding to the surfaces of potential target cells. Envelope protein was expressed amino terminal to the heavy-chain constant region of human immunoglobulin G containing the Fc receptor binding motif; the binding mediated by envelope determinants was distinguishable from the binding mediated by immunoglobulin Fc determinants. We found that the recombinant chimera bound to Vero, CHO, endothelial, and glial cells through envelope protein determinants and to monocytes and U937 cells by Fc-Fc receptor interactions. The highest level of binding was to Vero cells; binding was dose and time dependent and saturable. Examination of partial-length recombinant envelope proteins indicated that the binding motif was expressed between amino acids 281 and 423. Recombinant envelope protein inhibited infection of Vero cells by dengue virus, indicating the functional significance of the interaction of envelope protein and target cells in infectivity. These results suggest that envelope protein binding to a non-Fc receptor could explain the cell and tissue tropism of primary dengue virus infection.